Analysis of auditory brainstem response test time using narrow band level specific CE-Chirp and tone burst in infants - Mohamad Noor, Amnah; Dzulkarnain, Ahmad Aidil Arafat; Jamaluddin, Saiful Adli; Rahmat, Sarah; Mohd Zain, Siti Rashidah (IIUM Press, 2025)
Background and Aims: Despite advancements in auditory brainstem response (ABR) stimuli, the clinical application of narrow-band level-specific CE-Chirp (NB LS CE-Chirp) and the objective F-test multiple points (Fmp) algorithm remains underexplored, particularly in infant populations. These methodologies hold promise for improving the efficiency of ABR assessments and universal newborn hearing screening. This study evaluates the use of NB LS CE-Chirp as a test stimulus and the Fmp statistical algorithm as a stopping criterion to address prolonged ABR test durations.